Mammographic breast density : is there any association with positive family history of breast cancer? - Muhammed Nordin, Ellyda; Mohd Rus, Razman; Che Mohamed, Siti Kamariah; Hassan, Radhiana (2012)
INTRODUCTION: Breast cancer is the commonest overall cancer as well as the commonest cancer in women amongst all races. A higher incidence of breast cancer has been reported in women with dense breast parenchyma visible on mammogram and individuals with a family history of cancer. Previous study has reported that women with a family history of breast cancer tend to have dense breasts and this partially explains their increased risk of breast cancer.